К ВОПРОСУ О СЕМАНТИЧЕСКОЙ ОСНОВЕ ПЕРСОНИФИКАЦИИ - Мамадалиев Ахмадали; Каримова Нодирахон Абдурашидовна (International Journal of Innovative Technologies in Social Science, 2019)
This article discusses of the semantic basis of personification, for which, on the basis of oppositive methods and component analysis of words, semantic classes are established which are subjected to semantic transference of words and a common “meaning” (sema) that serves as the basis for the transference. In general, the meaning in the paradigmatic plan can serve as the semantic basis of the transference and in the syntagmatic plan as the semantic element of the connection of words.